PENERAPAN INFRARED REMOTE CONTROL DALAM MENGOPERASIKAN APLIKASI PADA SISTEM OPERASI WINDOWS XP - Ginta, Prama Wira; Utami, Feri Hari; Eicheng, Eicheng (UNIVED Press, 2013)
In the 20th century the technology associated with the collection. Processing and distribution of information have evolved considerably . Other technologies are experiencing rapid growth is utilizing the computer as a device that is versatile and can be especially helpful in facilitating human work . The development of computers from generation to generation until today more optimal performance, such as one of the advantages of multimedia, can steady MP3 songs. The development of electronic technology raises human tendency to make activities easier and practical , one of which is a wireless controller . On a computer that has a standard multimedia device , the operation should be done with a keyboard and mouse on the computer, so the user must always close and interact with both the input device. Because each piece of equipment has a different coding standards so users who use several different tools brand using multiple controllers. Based on the above introduction, the authors examine how to operate the application on the Windows XP operating system by using the infrared remote control .